Expression and Clinical Significance of SARS-CoV-2 Human Targets in Neoplastic and Non-Neoplastic Lung Tissues - Subbarayan, Karthikeyan; Ulagappan, Kamatchi; Wickenhauser, Claudia; Seliger, Barbara (Current Cancer Drug Targets, 2021)
Background: A higher incidence of COVID-19 infection was demonstrated in cancer patients, including lung cancer patients. This study was conducted to get insights into the enhanced frequency of COVID-19 infection in cancer. Methods: Using different bioinformatics tools, the expression and methylation patterns of ACE2 and TMPRSS2 were analyzed in healthy and malignant tissues, focusing on lung adenocarcinoma and data were correlated to clinical parameters and smoking history. Results: ACE2 and TMPRSS2 were heterogeneously expressed across 36 healthy tissues with the highest expression levels in digestive, urinary and reproductive organs, while the overall analysis of 72 paired tissues demonstrated significantly lower expression levels of ACE2 in cancer tissues when compared to normal counterparts. In contrast, ACE2, but not TMPRSS2, was overexpressed in LUAD, which inversely correlated to the promoter methylation. This upregulation of ACE2 was age-dependent in LUAD, but not in normal lung tissues. TMPRSS2 expression in non-neoplastic lung tissues was heterogeneous and dependent on sex and smoking history, while it was downregulated in LUAD of smokers. Cancer progression was associated with a decreased TMPRSS2 but unaltered ACE2. In contrast, ACE2 and TMPRSS2 of lung metastases derived from different cancer subtypes was higher than organ metastases of other sites. TMPRSS2, but not ACE2, was associated with LUAD patients’ survival. Conclusions: Comprehensive molecular analyses revealed a heterogeneous and distinct expression and/or methylation profile of ACE2 and TMPRSS2 in healthy lung vs. LUAD tissues across sex, age and smoking history and might have implications for COVID-19 disease.
Keywords: ACE2